Management of invasive aquatic weeds with emphasis on biological control in Senegal - Diop, Ousseynou (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2007)
In 1985 the Diama Dam was built near the mouth of the Senegal River to regulate flows during the rainy season and prevent the intrusion of seawater during the dry season. This created ideal conditions upstream of the dam wall for invasion by two highly invasive aquatic weeds, first by water lettuce Pistia stratiotes Linnaeus (Araceae) in 1993, and then by salvinia Salvinia molesta D.S. Mitchell (Salviniaceae) in 1999. This study was focused on the management of P. stratiotes and S. molesta. Following successes that were achieved elsewhere in the world, biological control programmes involving two weevil species were inaugurated against both weeds and research was focused on several aspects. These included pre-release studies to determine the weevils' host-specificity and impact on the plants in the laboratory, their subsequent mass-rearing and releases at selected sites and post-release evaluations on their impact on the weed populations in the field. Both programmes, which reprepresented the first biocontrol efforts against aquatic weeds in Senegal, proved highly successful with severe damage inflicted on the weed populations and complete control achieved within a relatively short time span. A laboratory exclusion experiment with N. affinis on P. stratiotes showed that in treated tubs, the weevil strongly depressed plant performance as measured by the plant growth parameters: mass, rosette diameter, root length, number of leaves and daughter plants whereas control plants were healthy. Field releases started in September 1994 and water coverage by P. stratiotes at Lake Guiers was reduced by 25% in January 1995 and 50% in April 1995. A general decline of 65% in water coverage by P. stratiotes was observed in June 1995 and by August 1995, eight months after releases P. stratiotes mats were destroyed. Further, although no releases were made there, good results were obtained within 18 months at Djoudj Park water bodies, located 150 km NW from Lake Guiers indicating the potential of the weevil to disperse long distances. In 2005, P. stratiotes reappeared and the weevil N. affinis has located and controlled all of these P. stratiotes recurrences after new releases. In 1999, S. molesta covered an estimated area of 18 000 ha on the Senegal River Left Bank and tributaries (Senegal) and 7 840 ha on the Senegal River Right Bank (Mauritania). Military and Civil Development Committee (CCMAD) and community volunteers made an effort to control S. molesta using physical removal, but this costly and labour-intensive approach was unsustainable. Hence, biological control was adopted by Senegal and Mauritania to manage the weed. Host range tests to assess feeding by C. salviniae on S. molesta and non-target plants and carried out on 13 crop species showed that no feeding damage was observed on the latter and weevils only fed on S. molesta. Field releases of some 48 953 weevils at 270 sites were made from early January 2002 to August 2002. Within one year, weevils were established and were being recovered up to 50 km from the release sites. In a case study conducted at one of the release sites, the S. molesta infestation was reduced from 100% to less than 3% 24 months after release. These results are discussed in the context of the weeds' negative impact on aquatic systems and riverside communities, and in the involvement of these communities in the programmes.
Keywords: Aquatic weeds -- Biological control -- Senegal; Invasive plants -- Biological control -- Senegal; Aquatic plants -- Biological control -- Senegal